Cobalt Ferrite Nanocrystallites for Sustainable Hydrogen Production Application - Rajendra S. Gaikwad; Sang-Youn Chae; Rajaram S. Mane; Sung-Hwan Han; Oh-Shim Joo (International Journal of Electrochemistry)
Cobalt ferrite, CoFe2O4, nanocrystalline films were deposited using electrostatic spray method and explored in sustainable hydrogen production application. Reflection planes in X-ray diffraction pattern confirm CoFe2O4 phase. The surface scanning microscopy photoimages reveal an agglomeration of closely-packed CoFe2O4 nanoflakes. Concentrated solar-panel, a two-step water splitting process, measurement technique was preferred for measuring the hydrogen generation rate. For about 5 hr sustainable, 440 mL/hr, hydrogen production activity was achieved, confirming the efficient use of cobalt ferrite nanocrystallites film in hydrogen production application.